The Influence of Relationship Marketing, Customer Satisfaction and Promotion on Customer Loyalty at PT BPRS Mitra Harmoni Malang City - Yudhanto, Ifani; Rachmawati, Ike Kusdyah; Bukhori, Mohammad (CV. Tripe Konsultan, 2024)
This research aims to determine the influence of Relationship Marketing, customer satisfaction and promotions on customer loyalty at PT BPRS Mitra Harmoni Malang City. The population in this research were customers of PT BPRS Mitra Harmoni Malang City, with a research sample of 100 respondents with a purposive sampling technique. The data collection techniques used were questionnaires, interviews and documentation. The analysis technique uses multiple linear regression with SPSS for Windows 26.0 statistical analysis. The research results show that relationship marketing, customer satisfaction and promotions have a positive and significant effect on customer loyalty. The research results show that relationship marketing has a positive and significant effect on customer loyalty at PT. BPRS Mitra Harmoni Malang City, satisfaction has a significant positive effect on customer loyalty to PT. BPRS Mitra Harmoni Malang City, promotions have a significant positive effect on customer loyalty at PT. BPRS Mitra Harmoni Malang City, and relationship marketing, satisfaction, promotions, influence PT customer loyalty BPRS Mitra Harmoni Malang City.